2020
DOI: 10.2147/jir.s276619
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Non-Coding RNA H19 Participates in Periodontal Inflammation via Activation of Autophagy</p>

Abstract: Purpose: Periodontitis is the leading cause of tooth loss. The role of long non-coding RNA (lncRNA) in periodontal inflammation remains unclear. The aim of this study was to investigate the role of lncRNA H19 in periodontitis and its possible regulation of autophagy in periodontitis. Material and Methods: Inflammation level was determined by quantitative reverse-transcription polymerase chain reaction (qRT-PCR) and enzyme-linked immunosorbent assay (ELISA) in periodontal ligament cells (PDLCs). Western blottin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…lncRNA H19 has been shown to be an important factor in autophagy [76,77] and has attracted attention for its interaction with periodontitis [78,79]. In PDLCs of ligated mice, autophagy was significantly increased and H19 expression was also significantly upregulated during inflammation [80].…”
Section: Evaluation In Periodontal Ligament Cellsmentioning
confidence: 99%
“…lncRNA H19 has been shown to be an important factor in autophagy [76,77] and has attracted attention for its interaction with periodontitis [78,79]. In PDLCs of ligated mice, autophagy was significantly increased and H19 expression was also significantly upregulated during inflammation [80].…”
Section: Evaluation In Periodontal Ligament Cellsmentioning
confidence: 99%
“…Table 3 presents 18 studies that investigated the role of lncRNAs in regulating cellular processes in PDL cells in the presence or absence of stimuli, including studies that compared H-PDL and P-PDL cells [ 60 , 61 , 62 , 63 , 64 , 65 ]. These studies also explored the role of lncRNAs in lipopolysaccharide (LPS)-induced inflammation [ 66 , 67 , 68 , 69 , 70 , 71 ], tumor necrosis factor-alpha (TNF-α)-induced inflammation [ 72 ], mechanical stress [ 73 , 74 , 75 ], hypoxia [ 76 ], and oxidative stress [ 77 ]. To review the outcomes of lncRNA involvement, cell proliferation, apoptosis, inflammatory responses, autophagy, migration, and root resorption were examined.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, research suggests that H19 could enhance the osteogenic differentiation of human bone marrow mesenchymal stem cell and bone formation via the miR‐675‐TGF‐β1‐Smad3‐HDAC signalling pathway, whereas knockdown of H19 suppresses these effects. 36 Recently, Guo et al 37 found that H19 participates in periodontal inflammation by activating autophagy. However, the potential role of H19 as a ceRNA in periodontitis has rarely been reported.…”
Section: Discussionmentioning
confidence: 99%